The Association between Imagination and Anxiety in the Times of the COVID-19 Pandemic. Issue 3 (3rd July 2021) - Zabelina, Darya L.; Clay, John Z.; Upshaw, Joshua D.
ABSTRACT: Imagination is relevant in many aspects of our lives and has been associated with creativity and overall cognitive development, yet imagination may also have a dark side. In two studies we examined the link between imagination, anxiety, and loneliness during the COVID-19 pandemic. US college students ( N = 101, Study 1) and participants from an international community sample ( N = 61, Study 2) were tested when that rates of COVID-19 cases were escalating. Across both samples, we found that spending more time in one's imagination was associated with elevated levels of anxiety. Furthermore, frequency of imagination interacted with loneliness in predicting changes in anxiety during, compared to before the pandemic. Specifically, lonely people who spent more time imagining experienced the largest increases in anxiety during, compared to before the pandemic. In Study 1 valence of imagination and changes in anxiety were also moderated by feelings of loneliness, although this effect was not replicated in Study 2. Results indicate that at least some features of imagination, particularly how much time people spend in imaginative states, may be associated with negative mood states, such as feelings of anxiety. Implications and future directions are discussed.